Earnings Quality and Corporate Governance: Evidence from UK - Wang, Hao (2020)
Earnings quality is vital to investors' decision-making. However, management is involved in earnings management activities due to various motivations. Corporate governance mechanisms could effectively prevent earnings management, which helps the improvement of the accuracy and transparency of financial reporting procedures. The dissertation investigates the relationship between board of directors and audit committee characteristics and earnings quality. This study explores the two mechanisms under agency theory and resource dependence theory. In the view of agency theory, the board and audit committees are monitors to prevent earnings management behaviours. In the view of resource dependence theory, they are channels that connect the firm with external resources such as skills, knowledge and expertise to improve firm performance. Both functions contribute to the enhancement of earnings quality. By using a sample of FTSE 250 companies listed in London Stock Exchange during 2015-2019, the study runs a regression model based on panel data. The study finds that board size and audit committee independence have positive relationships with earnings management. Besides, audit committee expertise is negatively related to discretionary accruals. Further, other characteristics including board independence, board meeting, board expertise, audit committee size, audit committee meeting have no effect on earnings management. This dissertation contributes to the understanding of the link between corporate governance mechanisms and earnings quality that a well-structured board and audit committee could improve earnings quality. This dissertation also provides some insights for practitioners and regulators of the effectiveness of those functions.